(3LGeY GHf jhfSs - (3CHh HcQ eMeO Hf YHO Gddg Hf jhfSs; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefYe HgOGjJg , GdeJee dfYeJg GeG HYO abO GfJgi Edi eG QZH ajg LeGYI ef WdHI GdYde HHdOfG ai GNJUGQ cJGH GdeOhfI hHSW CdaGXgG aSGQYJ Zdi Pdc hCONdJ ajg ebOeGJ CHhGH cJGH GdTjN CHj eMeO Hf CHj RjO s
(3BNQgG (B:s
(3aEPGge CMjGA ajJHYhf UhJ faNI GdUhQ , agh bhdg JYGdi (B: (3jJHYhf GdOGYi dGYhL dg (B) (3aPdc GdHYK hGdMTQ Edi Gddg JYGdi daUd GdbVGA , hgh bhdg JYGdi (B: ( (3Ke faN ajg CNQi (B) (3ced cJGH GdLfGFR hHJeGeI Je GdLRA GdChd hjJdhg GdKGfi cJGH GdUjGe s
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeI fajSIs
(3eDWQI HGdMeQIs
(3hHYV YHGQGJgG HGdRQbI hGdMeQI s
(3JedcgG QLd ef Hfi jYbhH CSeg eMeO eNJGQ ef aNP GdYeGe hGdJedc eDQN ai fSI (B1329 (3g` s
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs